Robust flight control for a quadrotor under external disturbances based on generic second order sliding mode control. Issue 12 (2022) - Benaddy, Abdellah; Labbadi, Moussa; Bouzi, Mostafa
Abstract: This paper presents a novel robust second order sliding mode control (RSOSMC) for tracking controller of a quadrotor with external disturbances. In addition, in order to perform the position and attitude tracking control of the quadrotor perfectly, the dynamical model of the quadrotor is divided into two subsystems, a subsystem fully actuated and an underactuated subsystem. The algorithm allows for rapid adaptation and stringent robustness of the quadrotor flight control in the presence of perturbations. Moreover, the proposed controller is based on the idea of second order sliding mode approach, which removes chattering in first-order sliding mode controllers. The finite-time stability and convergence of the proposed method are proved via the Lyapunov theory. To demonstrate the effectiveness of the suggested control approach, extensive simulation results are provided.